PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB DENGAN MENGGUNAKAN MODEL MEMORISASI - Undang Abdul Hamid (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This study aims to improve the mastery of Arabic vocabulary by using the memorization model. This type of research is a classroom action research conducted in three cycles. The subjects of this study were all students of class X-D of MAN 2 Pangandaran in the 2018/2019 academic year totaling 27 students. Data obtained from: student learning outcomes, student activity observations, student response journals, and observer field notes. The results showed that teacher activity increased from 2.49 in cycle I, to 2.92 in cycle II and 3.64 in cycle III. This means that the process of teaching vocabulary using the memorization model is very effective. The results of research on student activity increased from 2.37 in cycle I, 2.87 in cycle II, and 3.5 in cycle III. This means that students are very enthusiastic about the process of teaching vocabulary using the memorization model. The results of student journals have increased from 97.22% in cycle I, 98.14% in cycle II, and 100% in cycle III. This means that the process of teaching vocabulary using the memorization model received a positive response. The completeness of learning Arabic vocabulary in each cycle has increased. This can be seen from the test results, cycle I 85.18%, cycle II, 96.26%, cycle III 100%. The results showed that the memorization model could improve the learning outcomes of students' Arabic vocabulary mastery of class X-D MAN 2 Pangandaran.